Evaluation of the proper chest compression depth for neonatal resuscitation using computed tomography: A retrospective study. Issue 26 (2nd July 2021) - Lee, Juncheol; Lee, Dong Keon; Oh, Jaehoon; Park, Seung Min; Kang, Hyunggoo; Lim, Tae Ho; Jo, You Hwan; Ko, Byuk Sung; Cho, Yongil
Abstract : Abstract: This study was created to assess whether a 30-mm depth of chest compression (CC) is sufficient and safe for neonatal cardiopulmonary resuscitation. This retrospective analysis was performed with chest computed tomography scans of neonates in 2 hospitals between 2004 and 2018. We measured several chest parameters and calculated heart compression fraction (HCF) using the ejection fraction formula. We evaluated whether one-third of the external anterior-posterior (AP) diameter and HCF with them are the equivalent to 25-, 30-, 35 mm and HCF with them, respectively, and the number of individuals with over-compression (internal chest AP diameter − compressed depth <10 mm) to estimate a safe CC depth. We divided the patients into term and preterm groups and compared their outcomes. In total, 63 of the 75 included individuals were analyzed, and one-third of the external lengths was equivalent to 30 ± 3 mm ( P < .001). When the patients were divided into term (n = 53) and preterm (n = 10) groups, the equivalent depth was 30 ± 3 mm in the term group ( P  < .001) and 25 ± 2.5 mm in the preterm group ( P  = .004). The HCF with 30 mm was equivalent to that for one-third of the external length ( P  < .001). When we simulated CCs with a 30-mm depth, over-compression occurred more frequently in the preterm group (20%) compared to the term group (1.9%) ( P  = .014). A 30-mm depth could be appropriate for sufficient and safe neonatal resuscitation. Shallower CC should be considered in preterm babies.